Electronic wallet technology and the enabling environment of smallholder farmers in Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
Purpose - The purpose of this paper is to critically examine the impact of growth enhancement support scheme (GESS) on the enabling environment of smallholder farmers in sub-Saharan Africa. Its special focus is to investigate the GESS impact on access to rural farm credit and transport cost of smallholder farmers in the agricultural transformation agenda (ATA) in Nigeria. Design/methodology/approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional that describes and interprets what exist at present. A total of one thousand, two hundred farmers were sampled across the six geopolitical zones of Nigeria. Findings - Results from the use of a double-hurdle model indicate that the GESS has a significant impact on farmers' access to credit, but does not significantly affect rural farm transport cost, which subsequently influence the price of food in the country. Practical implication - This implies that if the federal government of Nigeria is to work towards an ideal agricultural transformation agenda, transport networks should be closely aligned with the GESS priorities to provide connectivity to rural areas that provide most of the country's agricultural o utput. Originality/value - This research adds to the literature on agricultural and rural development debate in developing countries. It concludes that embracing rural finance and transportation infrastructure should form the foundation of the ATA in Nigeria, which in turn would provide the enabling environment for more widespread rural economy in sub-Saharan Africa.
Keywords: Q10; Q14; L96; O40; O55; 330; Agricultural transformation agenda; Double-hurdle model; Smallholder farmers' enabling environment; Growth enhancement support scheme; Electronic wallet technology; Sub-Saharan Africa